(untitled) (Research, Society and Development, 2021)
This study evaluated the impact of climatic variables (precipitation, temperature and relative humidity) on the incidence of respiratory diseases represented by the ICD-10, in Manaus-AM. The gradual increase in the world population is directly related to the growth in the use of resources from the natural environment. As social inequality and environmental pollution are related to respiratory diseases, it is necessary to create public and private actions to control and monitor the level of related pollutants, in order to find alternatives to reduce the harmful effects on the population’s health. This study aims to analyze the number of people hospitalized for respiratory diseases in Manaus/AM during the period from 1998 to 2020 and the relationship of these diseases with atmospheric data. Data were obtained from public and private hospitals registered in the Unified Health System-SUS (DATASUS) through the admission form (AIH). The cost index of economic resources to the SUS follows the total number of cases, presenting a total of R 19,048.28, related to hospitalizations. After the analysis, there was a strong relationship between morbidity information and the registry of respiratory diseases and the humidity and temperature records in the region.